Explaining Eating Disorder Behaviour Among Chinese University Students Using The Extended Theory Of Planned Behaviourexplaining Eating Disorder Behaviour Among Chinese University Students Using The Extended Theory Of Planned Behaviour - Gao, Zeng (2024)
Adolescents’ unhealthy eating leads to them to adopt certain measures such as a diet, fasting and other behaviours that are likely to reduce body weight. The measures in turns lead to eating disorders and series of complications, such as impaired digestive system function, endocrine disorders, amenorrhea, hypoglycaemia, malnutrition, or physiological damage to various organ systems, and even life-threatening. It will affect the physical and mental health of the young and incurs high medical costs in one's country. In the long term it will be a physical and mental health issue that will increase medical expenses to treat it. Therefore, using the Theory of Planned Behaviour, this study was conducted to identify the factors that influence eating disorders among university students in the province of Gansu, China. Data was analysed using IBM SPSS and PROCESS 4.0 to answer all research questions developed. Results showed that there was significant difference in attitude towards physical activity, subjective norm, perceived behavioural control, body shape, self-esteem, and intention to engage in physical activities. between gender and body mass index (BMI). Gender and BMI also moderate the relationship between intention, body shape, self-esteem, and eating disorder. However, different gender and BMI in different attitudes (AT), subjective norms (SN), perceived behavioural control (PBC), body shape (BS), self-esteem (SE), and intention (IN) scores have significance. Family incomes only have a significant in self-esteem (SE).